Comprehensive Genetic Analysis of Monokaryon and Dikaryon Populations Provides Insight Into Cross-Breeding of Flammulina filiformis - Li, Hui; Shi, Lei; Tang, Weiqi; Xia, Weiwei; Zhong, Yingli; Xu, Xinyu; Xie, Baogui; Tao, Yongxin (Frontiers in Microbiology, 2022)
Flammulina filiformis is the most mature and productive edible fungus in industrialized cultivation. In recent years, its single variety and product convergence have seriously restricted the development of its industry. In this study, multiple representative F. filiformis strains were collected from the field and the factory, and the monokaryons and dikaryons were resequenced. Based on the high-throughput genotyping, the genetic diversity and population structure of 36 monokaryons, 23 dikaryons, and their combined populations were analyzed. The results showed that partial dikaryons and the two monokaryons components of the dikaryons showed a symmetric distribution pattern in principal component analysis, and the Eigen vector values of the dikaryons are infinitely close to the average values of the two monokaryons. Based on this model, we can predict the genetic pedigree and genotype of a monokaryons by sequencing only one monokaryon in a breeding dikaryotic strains. By analyzing the genetic pedigree of the two monokaryons, we can clearly trace the origin of their parents. This provides a good reference and evidence for inferring the history of cross-breeding and an effective method for guiding the selection of parents in cross-breeding.